The safety, tolerability and efficacy of pimavanserin tartrate in the treatment of psychosis in Parkinson's disease. (2nd June 2016) - Hermanowicz, Stefan; Hermanowicz, Neal
ABSTRACT: Parkinson's disease psychosis (PDP) is a common and often very disturbing component of Parkinson's disease (PD). PDP consists of hallucinations that are mainly visual and delusions that are often of a paranoid nature. These symptoms can be the most troubling and disruptive of all the manifestations of Parkinson's disease. Current treatment methods include the reduction of anti-Parkinson's medications, a strategy that may worsen the motor problems the medications are prescribed to alleviate, and the introduction of selected antipsychotic medications that carry with them the potential for troubling side effects and serious consequences. Pimavanserin has been developed and studied in clinical trials to specifically address Parkinson's disease psychosis and has been submitted to the U.S. Food and Drug Administration for its approval for this purpose. If this is granted, we believe the evidence of Pimavanserin efficacy, safety and tolerability will position this medication as the first choice for treatment of Parkinson's disease psychosis.